2015
DOI: 10.5897/jmpr2015.5764
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective medicinal plants used by the Gond and Bhill tribals of District Raisen Madhya Pradesh, India

Abstract: The ethnobotanical survey of the medicinal plants used in the management of jaundice (hepatic disorder) was carried out in the District Raisen of Madhya Pradesh. The herbalists, herb sellers and traditionalists were interviewed by the administration of questionnaires. Floristically, the area is placed in Malwa plateau region of Madhya Pradesh. Aims of the study were to document the medicinal plant resources and their use patterns by the tribal people. A total of 19 plant species belonging to 16 families were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…The use of medicinal plants can restore the body's ability to protect, regulate, and heal itself, promoting a physical, mental, and emotional well-being [14][15][16]. Various studies have shown the therapeutic effects of plants on fertility and infertility [17], hormonal disorders, hyperlipidemia [18], liver diseases [19], anemia [20], renal diseases [21], and neurological and psychiatric diseases [22]. Therefore, due to all the positive effects showed by medicinal plants, their potential use in cancer prevention and therapy has been widely suggested [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The use of medicinal plants can restore the body's ability to protect, regulate, and heal itself, promoting a physical, mental, and emotional well-being [14][15][16]. Various studies have shown the therapeutic effects of plants on fertility and infertility [17], hormonal disorders, hyperlipidemia [18], liver diseases [19], anemia [20], renal diseases [21], and neurological and psychiatric diseases [22]. Therefore, due to all the positive effects showed by medicinal plants, their potential use in cancer prevention and therapy has been widely suggested [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Who (Zereen and Sardar 2015 ) recorded Euphorbia helioscopia as dominant species in a sub-community in Narowal district Punjab. They (Haq et al xxxx; Zahoor et al 2015 ) also reported Cynodon dactylon as the leading member of the plant community. Similarly, Ali et al ( 2018 ) reported Arenaria serpyllifolia as the first dominant species in various communities from their studied area.…”
Section: Discussionmentioning
confidence: 99%
“…Cây Bông giấy (Bougainvillea spectabilis), một trong 18 loài thuộc chi Bougainvillea, được phân bố rộng rãi trên thế giới 1 . Trong y học cổ truyền, loài này được sử dụng để chữa trị viêm gan, tiêu chảy, ho 2,3 . Các nghiên cứu trước đây về hoạt tính sinh học trên loài này tập trung chủ yếu vào hoạt tính đái tháo đường.…”
Section: Giới Thiệuunclassified